Minat Futsal Putri pada Siswa Kelas X di SMA Negeri Kalisat: Minat Futsal Putri pada Siswa Kelas X di SMA Negeri Kalisat - Zulina, Ainurriza; Apriliyanto, Rizki; Hardovi, Bahtiar Hari (Universitas Hamzanwadi, 2025)
This study aims to determine the level of interest among female students at Kalisat State High School in futsal extracurricular activities. The type and approach of this study use a quantitative descriptive approach. The population in this study consists of all 88 students in grade X. The sample uses purposive sampling technique. The results of the study show that 13% of female students strongly agree with their interest in futsal. This means that a small proportion of female students have a strong interest in futsal. 46.2% of female students agree with an interest in futsal. This means that the majority of female students have an interest in futsal, though not strongly. 34% of female students disagree with an interest in futsal. This means that some female students do not have an interest in futsal. 6.8% of female students strongly disagree with an interest in futsal. Strong interest: 28% of female students have a strong interest in futsal (13% strongly agree + 15% of the 46.2% who agree are considered to have a strong interest). However, since there is no further explanation on how the 28% was calculated, it is unclear. No strong interest: 72% of female students do not have a strong interest in futsal (100% - 28%). Based on the interpretation of the data, it can be concluded that the majority of female students (72%) do not have a strong interest in futsal, while only a small proportion of female students (28%) have a strong interest in futsal.